Identification of Bird Diversity in the Campus Landscape of Institut Teknologi Sumatera (ITERA) As an Approach for Sustainable Campus Planning and Development - Anggi Mardiyanto; Bambang Prasetio (Penerbit Kemala Indonesia, 2020)
Institut Teknologi Sumatera (ITERA) is a campus that has the concept of developing a forest campus. Campus landscape which is quite extensive has the potential as the lungs of the city, supports the academic atmosphere and provides a comfortable space for campus residents. A healthy campus environment was characterized by a high level of biodiversity. One indicator of environmental health was the presence of birds. Birds are indicator species that are easily observed. The diversity of birds in the campus landscape illustrates the level of campus environmental health. This research aims to identify the diversity of birds in the ITERA campus landscape. This research has obtained 27 species of campus birds. The results of this study are expected to provide recommendation for sustainable campus planning and development.